Investigations on the lack of acquired immunity by the Javanese carp, Puntius gonionotus (Bleeker), against the crustacean parasite, Lernaea minuta (Kuang) - Kularatne, M.; Subasinghe, R.P.; Shariff, M. (1994)
During early 1991, an outbreak of lernaeosis in Puntius gonionotus occurred in a manmade lake in the Shah Alam recreational park in Selangor, West Malaysia. The parasite involved was identified as Lernaea minuta. An in vitro investigation was carried out to investigate the possible acquired immunity by P. gonionotus against the infection of L. minuta. The results revealed that fish acquire L. minuta infection regardless of whether they have recovered from previous infection, been injected with plasma from recovered fish or injected with plasma from naive fish. There was no significant difference (P<0·05) in the intensity of infection between the three groups. Histopathological observations confirmed that L. minuta causes mild inflammation and subsequent pathology in P. gonionotus, compared to that of L. cyprinacea, mainly due to its shallow penetration. The apparent lack of immunocompetence in P. gonionotus against L. minuta was attributed to the less potent pathology caused by the parasite on its host. © 1994 Academic Press. All rights reserved.